Methods and strategies for cassava technology transfer in China - Lin, Xiong; Li, Kaimian (International Center for Tropical Agriculture, 1995)
This paper describes the general situation and the existing problems of the extension of new cassava varieties, agronomic practices as well as processing technologies under the conditions of highly intensive agriculture in China. Cassava has been cultivated in China for over 170 years. Its production evolved from a small-scale backyard crop to large-scale commercial production; from a basic food crop to an upland cash crop used for animal feeding and industrial processing, while cropping systems gradually changed from predominantly monocropping to intercropping and crop rotations. However, the area under cassava production is decreasing due to the development of highly intensive agriculture on flat land and a policy of reforestation on steep slopes. Therefore, it is very important to improve the extension of new cassava technologies so as to increase yields and the production value of cassava. Presently, several research institutes, such as SCATC, UCRI and GSCRI, have cassava breeding programs. Since the 1960s SCATC has collected, evaluated, propagated and recommended some good varieties, such as SC205 and SC201, for release and promotion among cassava farmers in southern China. Recently, a national cassava cooperation network, led by research institutes, has been established with the objective of introducing, propagating, demonstrating and testing of promising breeding lines in regional trials. This is a combination of research and production, simultaneously testing, demonstrating and promoting good varieties with the help of agricultural extension units and financed by agricultural authorities in the government. Two new high-yielding varieties, namely SC124 and Nanzhi-188 (the latter introduced from CIAT in tissue culture), have recently been released and are now grown on about 26,000 ha with an average yield of 30-40% over previous varieties, which represents an increase in income of 12-15 million yuan. Similarly, the intercropping or rotational cropping of cassava with pasture species, such as Stylosanthes 184, increased gross income 23-43% and reduced soil erosion by 14-27%. Research on cassava further-processing, conducted by the Guangxi Nanning Cassava Technical Development Centre, has also contributed greatly to increase the value of cassava-based products and to expand marketing channels, both at home and abroad.